Evolution stages of aircraft manufacturing firms. Issue 3 (13th January 2019) - Reis, Anabela; Siddiqi, Afreen; de Weck, Olivier
Abstract: Aeronautics is one of the highest value‐adding industrial sectors in an economy, and many regions have sought to develop aeronautics industries for economic diversification. Aircraft production, however, is complex and capital‐intensive, and efforts to establish aircraft manufacturing firms have led to mixed results. Here, we present a study of development of six international aeronautical manufacturing firms, across four continents, using a mixed‐method approach. Using empirical quantitative data and results from 103 semistructured interviews with senior executives and policy makers, we identify a set of discrete stages: inception, base production, competitive growth, inventive development, and maturity that characterize the evolution pathways of aeronautics firms. We find that firms do not necessarily follow a linear development path, and they can jump and skip stages or may regress back to earlier stages under financial or other pressures. We find that aeronautics firms are more likely to reach a self‐sustaining maturity stage once they establish independent contracts with multiple partners and are able to develop their own technologies. The results indicate that firms should establish strategies to acquire independent contracts through competitive bidding and should plan for achieving innovation capabilities early on as this is crucial for their long‐term viability.